Remember God - Downs, Annie F., 1980- (B & H Publishing Group, 2018)
"I know God is loving; I know He is good; I believe He is big and powerful. But sometimes I wonder if He is really kind-- really deeply always kind. Is He? Christians love to talk about how God is in control, but that's harder to grasp when things aren't going like you thought they would, when your life looks quite different than you imagined. For centuries, God's people have been building altars to Him--to remind themselves and the people around them of His work. His goodness. His kindness. Stacks of stones. Altars. Temples. Cathedrals. Why? Because they believed God and wanted to remember Him. In the back of my mind, God reminds me that He is the same trustworthy God--the One who always finishes the stories he starts. And this is my story--of wrestling with our God who gives a limp and a blessing. A God who is always kind even when my circumstances feel the opposite. God is who He says He is. He is kinder than you imagine. In a world where it is easy to forget who He is, we will not. We will remember God."--Page [4] of cover.